If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -1(6x + 8) = -3 Reorder the terms: 7x + -1(8 + 6x) = -3 7x + (8 * -1 + 6x * -1) = -3 7x + (-8 + -6x) = -3 Reorder the terms: -8 + 7x + -6x = -3 Combine like terms: 7x + -6x = 1x -8 + 1x = -3 Solving -8 + 1x = -3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 1x = -3 + 8 Combine like terms: -8 + 8 = 0 0 + 1x = -3 + 8 1x = -3 + 8 Combine like terms: -3 + 8 = 5 1x = 5 Divide each side by '1'. x = 5 Simplifying x = 5
| 12-8x=172-43x | | 14x+(3x+10)=180 | | 5(8)+2(8)+6(6)=92 | | 9(8)+9(8)+6(6)=180 | | 2x+3x-15=20 | | 0.15x+0.05(4-x)=0.10(-6) | | -5(2x+3)+8x-9=6x-8(x+3) | | 6(z-7)=7z-4 | | 3x+7=3(x-6) | | 7u^2-6x-1=0 | | -(14-a)= | | 5(8)+8(8)-9(6)=50 | | 89-3x=7-8x | | X^3+4x^2+21x=0 | | -5(7)-9(9)+2(0)=5 | | 3r^2+270=0 | | -9(7)+8(9)+8(0)=12 | | -8(7)+2(9)+6(0)=-38 | | 4x+31=14x-59 | | 2b-6= | | 4b-6=6-2b | | 7-y=1 | | x^2-7x=x(8+x) | | 2a-3=-3a+7 | | 3(2x-7)=-9 | | 12+-3x=-7x-48 | | 7x+10+5x-8x= | | 6x+33=14x-63 | | 6q+5q= | | -3q=5 | | (5x-22)(2x+35)= | | -8.4=c-3.1 |